2016
DOI: 10.1016/j.appet.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

High perceived stress is associated with unfavorable eating behavior in overweight and obese Finns of working age

Abstract: b s t r a c tStress-related eating may be a potential factor in the obesity epidemic. Rather little is known about how stress associates with eating behavior and food intake in overweight individuals in a free-living situation. Thus, the present study aims to investigate this question in psychologically distressed overweight and obese working-aged Finns. The study is a cross-sectional baseline analysis of a randomized controlled trial. Of the 339 study participants, those with all the needed data available (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 49 publications
5
63
4
3
Order By: Relevance
“…As hypothesized, stress in the workplace was related to eating both more food in general and more junk food specifically. Additionally, participants with low weight self‐efficacy were more likely to report eating in response to stress, which makes sense in light of past research showing that individuals with higher levels of stress or work‐related burnout tend to eat less intuitively and with less control . With respect to work performance, higher levels of self‐rated work impairment due to binge eating were also related to eating in response to stress.…”
Section: Discussionmentioning
confidence: 74%
“…As hypothesized, stress in the workplace was related to eating both more food in general and more junk food specifically. Additionally, participants with low weight self‐efficacy were more likely to report eating in response to stress, which makes sense in light of past research showing that individuals with higher levels of stress or work‐related burnout tend to eat less intuitively and with less control . With respect to work performance, higher levels of self‐rated work impairment due to binge eating were also related to eating in response to stress.…”
Section: Discussionmentioning
confidence: 74%
“…Elixir study was a multi-centre lifestyle intervention aimed to enhance the psychological well-being of 339 individuals with overweight/obesity and self-reported stress symptoms 19 . In this study, higher perceived stress was associated with less physical activity 20 and unfavourable eating behaviours, such as higher dependency on emotional and rewarding properties of food rather than physiological hunger cues and less consumption of wholegrain products 21 . Conversely, study participants with higher physical activity recovered better from stress 22 .…”
mentioning
confidence: 55%
“…The Transactional Model of Stress and Coping suggests that stress is associated with people's health behaviors that are influenced by how they appraise and cope with their stress [19]. Studies have linked occupational stress to increased likelihood of abnormal eating behaviors (e.g., emotional eating) [20][21][22] and greater intake of low-nutrient food (e.g., sweetened snacks) [23][24][25][26]. Time availability for food ingestion has also been linked to people's healthy eating behaviors [27][28][29] with time pressure contributing more to workers' decisions on food consumption compared to appetite [30].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research work has suggested that occupational stress and time availability at work influence workers' eating behaviors [20][21][22][29][30][31]. This research has focused mainly on how stress or stressful events are related to unhealthy eating behaviors or intake of low-nutrient food, but it remains unclear to what extent occupational stressors (e.g., workload) may contribute to SSB consumption as meal substitutes during work.…”
Section: Introductionmentioning
confidence: 99%